peraturan perusahaan Peraturan Perusahaan dan Peraturan Kerja Bersama Pada Perusahaan Manufaktur Di Kota Batam - Rano Ardiansyah; Julius Kurnaedi; Jimmy Lim; Calvin; Alden Nelson (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
This study discusses company regulations (PP) and collective labor agreements (PKB) in employment relations between employers and employees. PP is a written regulation made by a company to regulate the obligations and rights of the company and employees. While PKB is an agreement reached between employers and trade unions regarding obligations, rights, and conditions of employment. The method used in this study is quantitative method with descriptive data analysis. The results showed that PP is determined unilaterally by employers, while PKB involves negotiations between employers and trade unions. PP is valid for a maximum of 2 years and must be renewed, while PKB is valid for a maximum of 2 years and can be extended. Manufacturing companies are the focus of this study, and the preparation of PP is needed to enforce the level of compliance with laws and regulations. PKB becomes a reference for trade unions and companies in determining rights and obligations. PP and PKB have an important role in creating good and harmonious industrial relations.